أشكال الاغتراب وتمظهراته في رواية: "باردة كأنثى" لإسماعيل يبرير - رفاد, مروة; طرش, علي (University of Eloued جامعة الوادي, 2024)
تفشّت ظاهرة الاغتراب في العصر الحالي بشكل لافت للانتباه؛ وذلك لوجود مستجدّات تضعف صلة الإنسان بنفسه وبكلّ ما حوله. وبما أنّ الرّواية تقتنص من روح عصرها ما يخدمها؛ فقد عبّرت عن هذه الظّاهرة بأمانة، حيث نقلت تفاصيل هذه المعاناة فنّيا. وهو ما نجده في: "باردة كأنثى لإسماعيل يبرير" التي تستفزّ المتلقّي انطلاقا من غلافها وعنوانها وصولا إلى المتن، الأمر الذي يفرز استفهاما حول مدى تناغم وانسجام هذه العناصر فيما بينها لتصوير الشّخصيّة الرّوائيّة المغتربة. وقد توصّل البحث إلى عدّة نتائج أهمّها أنواع الاغتراب، وهي: النّفسيّ، الاجتماعيّ، الوجوديّ، الزّمنيّ، المكانيّ، الثّقافيّ، الدّينيّ، السّياسيّ. Abstract: The phenomenon of alienation has remarkably spread recently. This is due to the presence of some developments that weaken the human’s connection with himself and everything around him. Since the novel captures what serves it from the spirit of its era, then it expressed this phenomenon; as it conveyed the details of this suffering artistically. This is what we find in: “Barida Ka Ontha” by Ismail Yabrir,” that provokes the recipient, starting from its cover and title, all the way to the text, which raises a question about the extent of harmony between these elements to depict the alienated fictional character. The research has reached several results, most important is the types of alienation which are: psychological, social, existential, temporal, spatial, cultural, religious, and political
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي
Keywords: ظاهرة; اغتراب; رواية; باردة كأنثى